Role of Rituximab Addition to First-line Chemotherapy Regimens in Nodular Lymphocyte-predominant Hodgkin Lymphoma: A Study by Fondazione Italiana Linfomi. Issue 4 (4th April 2023) - Gotti, Manuel; Sciarra, Roberta; Pulsoni, Alessandro; Merli, Francesco; Luminari, Stefano; Zerbi, Caterina; Trentin, Livio; Re, Alessandro; Rusconi, Chiara; Viviani, Simonetta; Rossi, Andrea; Cocito, Federica; et al.
Abstract : Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is a rare entity whose neoplastic cells retain a B-cell phenotype with expression of CD20. Radiotherapy is recommended for favorable stage IA disease while for other stages guidelines suggest therapeutic strategies similar to those used for classic HL. The role of rituximab, although quite widespread, is not completely elucidated. We retrospectively analyzed baseline characteristics of 308 consecutive patients with NLPHL diagnosed in 19 Italian centers from 2000 to 2018. With a median follow-up of 8.4 years (interquartile range: 4.5–12.4) for treated patients, median overall survival (OS) was not reached and estimated 5-year OS was 97.8% and 5-year progression-free survival (PFS) was 84.5%. Five-year cumulative incidence of histological transformation was 1.4%, 95% confidence interval (CI), 0.5%-3.8%. After adjusting for lymphocyte count, splenic involvement, bulky disease and B symptoms (fever, drenching night sweats, unintentional loss >10% of body weight within the preceding 6 months), patients with stage II or more showed superior PFS with immunochemotherapy in comparison to chemotherapy alone (hazard ratio = 0.4, 95% CI, 0.2-0.8; P = 0.015). Our data suggest an advantage of the use of rituximab combined with chemotherapy ± radiotherapy in the treatment of stage II–III–IV NLPHL. Abstract :